ANALISIS PERBANDINGAN MOTIVASI KERJA DAN KEPUASAN KERJA BERDASARKAN GENDER PADA PUSKESMAS UTAN KABUPATEN SUMBAWA - Baiq Ertin Helmida; Rosyia Wardani; Harianto Harianto (Master of Management, Mataram University, 2021)
This study aims to analyze differences in work motivation and job satisfaction based on gender in the Utan Health Center in Sumbawa Regency. The subjects in this study were all employees of the Utan Health Center in Sumbawa Regency. This study used a sample of 60 employees, consisting of 15 male employees and 45 female employees. The sampling technique in this study uses Disproportionate stratified random sampling and to test the hypothesis MANOVA analysis tools are used with a significance level of 5%. The results of the data analysis show that there is a significant difference in the work motivation of male employees and female employees at Puskesmas Utan, Kabupaten Sumbawa, where the significance value is 0.002 <0.05. Meanwhile, the results of the job satisfaction variable showed that there was no significant difference between male employees and female employees at the Puskesmas, Kabupaten Sumbawa, where the significance value was 0.138> 0.05.Keywords:Analysis Differences in Work Motivation and Job Satisfaction Based on Gender